2021
DOI: 10.1021/acscentsci.1c00616
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Hydrazine Probes for Protein Profiling of Electrophilic Functionality in Therapeutic Targets

Abstract: Most known probes for activity-based protein profiling (ABPP) use electrophilic groups that tag a single type of nucleophilic amino acid to identify cases in which its hyper-reactivity underpins function. Much important biochemistry derives from electrophilic enzyme cofactors, transient intermediates, and labile regulatory modifications, but ABPP probes for such species are underdeveloped. Here, we describe a versatile class of probes for this less charted hemisphere of the proteome. The use of an electron-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 52 publications
3
58
0
Order By: Relevance
“…ABPP principles and ‘reverse-polarity’ probes have been employed to study electrophilic post-translational modifications, such as N-terminal pyruvoyl and glyoxylyl modifications, that can react with hydrazine-containing compounds 197 . Hydrazine-based probes have also been used to help identify and characterize ligands for proteins with electrophilic cofactors or post-translational modifications 198 , 199 .…”
Section: The Covalent Drug Discovery Toolboxmentioning
confidence: 99%
“…ABPP principles and ‘reverse-polarity’ probes have been employed to study electrophilic post-translational modifications, such as N-terminal pyruvoyl and glyoxylyl modifications, that can react with hydrazine-containing compounds 197 . Hydrazine-based probes have also been used to help identify and characterize ligands for proteins with electrophilic cofactors or post-translational modifications 198 , 199 .…”
Section: The Covalent Drug Discovery Toolboxmentioning
confidence: 99%
“…For instance, point mutations or deletion variants are very commonly included in activity studies to give indication for the function of particular amino acid residues. Also, hydrazines have recently been introduced as novel, versatile nucleophilic in situ probes for the study of (among others) AlkBH and related enzymes by activity‐based protein profiling (ABPP) [28] . While there are examples of these methods briefly introduced in several of the following sections where appropriate, this frequent element is not described as a technique in the context of this review in detail.…”
Section: Structural Studies and Substrate Interactionsmentioning
confidence: 99%
“…Also, hydrazines have recently been introduced as novel, versatile nucleophilic in situ probes for the study of (among others) AlkBH and related enzymes by activity-based protein profiling (ABPP). [28] While there are examples of these methods briefly introduced in several of the following sections where appropriate, this frequent element is not described as a technique in the context of this review in detail. Further, the mutual dependence between detailed in vitro investigation of an enzyme and experiments in vivo (e. g., by gene deletion studies to learn about its physiological function) is not addressed as in vivo studies are beyond the scope of this article.…”
Section: Structural Studies and Substrate Interactionsmentioning
confidence: 99%
“…In 2021, Matthews and co-workers developed a novel class of organohydrazine mechanism-based probes. 119 Previous studies had demonstrated that organohydrazine probes could be used as nucleophiles for reverse polarity protein profiling; 120 however detection of some unexplained adducts suggested a secondary labeling pathway. Examination revealed that enzymes which bound oxidizing cofactors at their active sites could oxidize organohydrazine probes to form a carbon centered radical for covalent protein–probe cross-linking ( Figure 5 f).…”
Section: Endogenous Inductionmentioning
confidence: 99%
“…In 2021, Matthews and co-workers developed a novel class of organohydrazine mechanism-based probes . Previous studies had demonstrated that organohydrazine probes could be used as nucleophiles for reverse polarity protein profiling; however detection of some unexplained adducts suggested a secondary labeling pathway.…”
Section: Endogenous Inductionmentioning
confidence: 99%